A Sense of Pride and Representations: Figures of Speech Analysis on Selected Poems - Joseph C. Cuenca; Hanzen D. Tomatao; Maureen A. Logronio (PT ARRUS Intelektual Indonesia, 2024)
This study presents an analysis of the selected poems of Restituto Acapulco, a native of Ozamiz City, Misamis Occidental. This study utilized a textual analysis focused on figures of speech and the implications of five selected poems to culture and religion. The figures of speech used in 5 poems analyzed are synecdoche, hyperbole, metaphor, personification, simile, metonymy, apostrophe, repetition, imagery, alliteration. This study has revealed the representation and meanings pertaining to the religious culture specifically faith and religious activities of the devotees and residents of Ozamiz City, Misamis Occidental, Philippines.